A SOCIO-PHILOSOPHICAL ASPECT OF FAMILY VALUES - Xakimov A.A (Western European Studies, 2024)
The article attempts to explore family values. The family is the object of a comprehensive study of various sciences in general, philosophy in particular. The value approach is used in various philosophical systems
Keywords: family; value; tradition; spiritual heritage